Metabolic profile and atherogenic indices of rats treated with Tamarindus indica and Mentha piperita juice. - Sandra Maria Barbalho; Silvia Cristina Cerini Trevisan; Aline Pereira Paes Menezes; Elen Landgraf guiguer; Marie Oshiiwa; Vanessa Sellis; Adriana Fiorini (International Journal of Phytomedicine, 2017)
Changes in diet, physical inactivity and stress contribute to obesity, cardiovascular disease and atherosclerosis. Literature shows that bioactive compounds may result in benefits to human health. The aim of this study was to evaluate the glycemic, lipid profile and atherogenic indices of Wistar rats treated with Mentha piperita and Tamarindus indica juice. Animals received food and water ad libitum and were divided into 3 groups: control group (G1) that received 0.5 mL of water twice daily; Mentha group (G2) treated with 0.5 mL of mint juice and group treated with Tamarindus indica juice (G3), that received 0.5 mL of tamarind juice twice daily for 40 days. Groups G1, G2 and G3 received the drinks by intragastric rout. After this period the animals were sedated with sodium pentobarbital for blood collection and evaluation of the biochemical profile: total cholesterol, HDL-c, LDL-c, triglycerides and glucose. Atherogenic indexes were also calculated. The results showed a reduction of total cholesterol, LDL-c, triglyceride, body weight and atherogenic indices; and increase in the levels of HDL-c. We may suggest that the use of mint and tamarind juice can positively affect the biochemical parameters and reduce the atherogenic indexes of Wistar rats.